Management of green procurement in small and medium-sized manufacturing enterprises in developing economies - Tetiana Ivanova (Amfiteatru Economic Journal, 2020)
This article explores the issue of managing green procurement at the level of small and medium-sized enterprises in developing countries. Green procurement remains a relatively new trend for small and medium-sized enterprises (SMEs). Therefore, a thorough analysis of this issue is a topic theme. In this perspective, the following hypotheses are highlighted: green procurement affects the competitiveness of an enterprise, its economic indicators, the environment and society. The data collected from SMEs in Kyiv and Kyiv region. As a result, we analysed the questionnaires provided by the managers of 181 companies operating in different industries and different forms of ownership. Factor analysis was conducted to evaluate the scales used in the study, and hypotheses were tested using structural equation modelling. The results show that green procurement has a positive impact on competitiveness, economic performance of SMEs, the environment and society. Therefore, small and medium-sized enterprises in developing countries should pay attention to the development and implementation of green supplies, as this will have a positive impact on their performance. The research conducted can serve as a benchmark for conducting similar studies on other enterprises.
Keywords: L60; O35; Q56; 330; green procurement; green supply chain; enterprise competitiveness; economic performance; ecological environment; impact on society